Expression Profile of Toll-Like Receptor mRNA in an Indigenous Aseel Breed of Chicken in India - Raj, G. Dhinakar; Rajanathan, T.M. Chozhavel; Kumanan, K.; Elankumaran, S. (International Journal of Poultry Science, 2009)
Expression profile of chicken six Toll-like Receptor (TLR) mRNAs were analyzed in the heterophils, lungs, liver, spleen, duodenum, caecal tonsils and kidneys of 12-weeks old indigenous village chicken in India, using reverse transcription polymerase chain reaction (RT-PCR). TLR 2 type 1 mRNA was expressed in lungs, liver, spleen, duodenum and caecal tonsils. TLR2 type 2 mRNA was expressed only in the lungs. TLR 3 mRNA was expressed in lungs, liver, spleen and caecal tonsils. TLR 4 mRNA was expressed only in lungs, liver and spleen. TLR 5 and TLR 7 mRNAs were expressed in all the tissues examined. With respect to tissues, heterophils and lungs expressed all the TLR mRNAs examined while kidneys expressed only TLR 5 and TLR 7 mRNAs. All the TLR amplified PCR products were partially sequenced and showed high homologies with the available chicken (commercial) TLR gene sequences. There could be a possibility of correlation between TLR mRNA expressions with higher levels of innate immunity seen in indigenous village breeds of chickens.